CVD synthesis of highly graphitized single-walled carbon nanotubes using nitrogen-pretreated Fe-Mo/MgO catalyst - Patil, Gaurav; Sarode, Chetan; Patil, Rahul; Gokhale, Suresh (Chemistry Letters, 2012)
Single-walled carbon nanotubes (SWNTs) with highly graphitized structure were synthesized by thermal chemical vapor deposition using an improved nitrogen-pretreated Fe-Mo/MgO catalyst. The effects of nitrogen pretreatment of Fe-Mo/MgO on the structure and properties of SWNTs were studied by TEM, Raman spectroscopy, and TGA. The investigations revealed that the nitrogen pretreatment of the catalyst promoted the growth of SWNTs. It also enhanced the structural features and thermal properties of SWNTs.